About the Stability and Positivity of a Class of Discrete Nonlinear Systems of Difference Equations - M. De la Sen (Discrete Dynamics in Nature and Society)
This paper investigates stability conditions and positivity of the solutions of a coupled set of nonlinear difference equations under very generic conditions of the nonlinear real functions which are assumed to be bounded from below and nondecreasing. Furthermore, they are assumed to be linearly upper bounded for sufficiently large values of their arguments. These hypotheses have been stated in 2007 to study the conditions permanence.